Nonalcoholic fatty liver disease contributes to subclinical atherosclerosis: A systematic review and meta‐analysis - Zhou, Yao‐Yao (Hepatol Commun, 2018)
Nonalcoholic fatty liver disease (NAFLD) is associated with an increased risk of atherosclerotic cardiovascular disease. In our meta‐analysis, we aimed to assess the correlation of NAFLD and four surrogate markers of subclinical atherosclerosis. PubMed, Embase, and the Cochrane Library were searched up until April 2017. Original studies investigating the association between NAFLD and subclinical atherosclerosis were included. The outcome data were extracted and pooled for the effect estimate by using a random‐effects model. We used the Newcastle‐Ottawa Quality Assessment Scale to assess the quality of the included studies. Of the 434 initially retrieved studies, 26 studies involving a total of 85,395 participants (including 29,493 patients with NAFLD) were included in this meta‐analysis. The Newcastle‐Ottawa Quality Assessment Scale scores suggested the included studies were of high quality. The pooled effects estimate showed that subjects with NAFLD exhibited a significant independent association with subclinical atherosclerosis compared to the non‐NAFLD group (odds ratio, 1.60; 95% confidence interval, 1.45‐1.78). Subgroup analysis suggested that the presence of NAFLD yielded a remarkable higher risk of increased carotid artery intima‐media thickness/plaques, arterial stiffness, coronary artery calcification, and endothelial dysfunction with odds ratios (95% confidence interval) of 1.74 (1.47‐2.06), 1.56 (1.24‐1.96), 1.40 (1.22‐1.60), and 3.73 (0.99‐14.09), respectively. Conclusion: Our meta‐analysis revealed a close link between NAFLD and subclinical atherosclerosis in light of four different indices. Patients with NAFLD might benefit from screening and surveillance of early atherosclerosis, which would facilitate the prediction of potential cardiovascular disease burden, risk stratification, and appropriate intervention in the long term. (Hepatology Communications 2018;2:376‐392)